Uji Teratogen Ekstrak Akar Jarong (Stachytarpheta jamaicensis (L.) Vahl.) terhadap Sistem Reproduksi Mencit (Mus musculus L.) Betina - Agustinus Renyoet; Raynard C. Sanito (Jurnal Biologi Papua, 2011)
This study aim to determine the teratogens effect of jarong (Stachytarpheta jamaicensis (L.) Vahl) roots extract on the reproductive system of mice (Mus musculus L.) female Swiss Webster organogenesis during pregnancy.The method used in this study is the method of extraction and  examination of vaginal smears.. The experiment was conducted in August-December 2010, at the Laboratory of Zoology, Department of  Biology  Cenderawasih University, Jayapura. The Experiment was carried out by dividing the 20 female mice into 4 groups. One group is a control group and with no treatmen and the  other 3 groups  were tretaed with oral treatments.. The results obtained in the qualitative descriptive analysis. It could be concluded that ethanol extract of jarong (Stachytarpheta jamaicensis (L.) Vahl) roots cause of accidental poisoning in mice, embryotoxic and causes the effects of teratogens. Key words: Jarong (Stachytarpheta jamaicensis (L.) Vahl), teratogens effect, mice (Mus musculus L.).